2022
DOI: 10.1016/j.isci.2021.103569
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary modeling reveals enhanced mutational flexibility of HCV subtype 1b compared with 1a

Abstract: Hepatitis C virus (HCV) is a leading cause of liver-associated disease and liver cancer. Of the major HCV subtypes, patients infected with subtype 1b have been associated with having a higher risk of developing chronic infection and hepatocellular carcinoma. However, underlying reasons for this increased disease severity remain unknown. Here, we provide an evolutionary rationale, based on a comparative study of fitness landscape and in-host evolutionary models of the E2 glycoprotein of HCV subtypes 1a and 1b. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 95 publications
(178 reference statements)
0
1
0
Order By: Relevance
“…In an undersampled regime, these correlations are expected to be weak and multiple rounds can be treated as independent samples. The approach shares similarities with various studies where a Potts model is inferred from a Multiple Sequence Alignment (MSA) of observed mutated viruses [44][45][46][47][48]. This inference is typically used to establish a prevalence landscape, often considered a surrogate for the intrinsic fitness landscape.…”
Section: Methodological Advancements and Limitationsmentioning
confidence: 99%
“…In an undersampled regime, these correlations are expected to be weak and multiple rounds can be treated as independent samples. The approach shares similarities with various studies where a Potts model is inferred from a Multiple Sequence Alignment (MSA) of observed mutated viruses [44][45][46][47][48]. This inference is typically used to establish a prevalence landscape, often considered a surrogate for the intrinsic fitness landscape.…”
Section: Methodological Advancements and Limitationsmentioning
confidence: 99%